DINAMIKA JEJARING AKTOR PADA KAWASAN PERMUKIMAN MULTI ETNIS JEMBATAN BESI, TAMBORA - Purwa Septa Dupit T; Joko Adianto (Media Bina Ilmiah, 2024)
Jembatan Besi commercial area is known as the densest settlement area located in West Jakarta. The dynamics of this area can be seen in how each actor can be related and mutually influential in the activities of finding a source of livelihood. The existence of ethnic diversity in this area is one of the interesting things to research. Of course, the connection between actors and the influence of ethnic diversity can form a pattern that can be mapped. Spatial patterns and spontaneous responses of actors in making dispositions when facing spatial conflicts and the character of multi-ethnic commercial areas raise questions related to the habitus formed by each actor in a social network in an effort to defend themselves. The aim of this research is to reveal the dynamics of actor networks in the Jembatan Besi multiethnic commercial area. This qualitative research uses a case studies approach. The results of the analysis show that there is a connection between ethnicity and the spontaneous responses of the actors to defend themselves so they can form networks that strengthen and influence each other.